2022
DOI: 10.1002/anie.202210184
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient and Selective Recognition of Dicyanoaurate(I) by a Bambusuril Macrocycle in Water

Abstract: Dicyanoaurate(I) anion, [Au(CN) 2 ] À , plays a central role in the current industrial production of gold, as its extraction from crude ore samples represents the most money-consuming step. Herein, we present the strongest host-guest recognition of dicyanoaurate anion using the bambusuril receptor in water, a highly competitive solvent. The micromolar stability of such a complex facilitated the up to date most efficient supramolecular stripping of dicyanoaurate from activated carbon at ambient temperature. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…In 1 H NMR aqueous-solution spectra, the complexation-induced chemical shifts confirmed the formation of inclusion complexes, as indicated by the large downfield shifts of the inner protons of γ-CD. In addition, 77 Se and 125 Te NMR experiments supported the complexation pattern in solution. The binding affinities of the anions to γ-CD were determined using ITC experiments, which showed that the complexation is enthalpically driven, in agreement with the chaotropic effect.…”
Section: Reviewmentioning
confidence: 63%
See 2 more Smart Citations
“…In 1 H NMR aqueous-solution spectra, the complexation-induced chemical shifts confirmed the formation of inclusion complexes, as indicated by the large downfield shifts of the inner protons of γ-CD. In addition, 77 Se and 125 Te NMR experiments supported the complexation pattern in solution. The binding affinities of the anions to γ-CD were determined using ITC experiments, which showed that the complexation is enthalpically driven, in agreement with the chaotropic effect.…”
Section: Reviewmentioning
confidence: 63%
“…71 The macrocycle was later intensively investigated for its binding to halides with high affinity and selectivity (see below). 38,39,[72][73][74][75][76][77] Recent developments in large anion binding and mechanistic interpretations (after 2015)…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…27 They function as efficient anion transporters, 27 supramolecular hydrogels, 28 as rotaxane constituents, 29 and in the selective recognition of diacyanoaurate(I). 30 Majority of bambusurils are achiral. 15 However, the synthesis of the first chiral bambusurils was recently reported, and their ability to bind enantiomers of biologically relevant compounds with selectivity exceeding 3 was demonstrated.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Bambus[6]­urils show high association constants ranging up to 10 11 M –1 in organic solvents . They function as efficient anion transporters, supramolecular hydrogels, as rotaxane constituents, and in the selective recognition of diacyanoaurate­(I) …”
Section: Introductionmentioning
confidence: 99%